2016
DOI: 10.1103/physrevlett.117.142501
|View full text |Cite
|
Sign up to set email alerts
|

Branching and Fragmentation of Dipole Strength inTa181in the Region of the Scissors Mode

Abstract: In recent measurements of the scissors mode in radiative decay experiments, transition strengths were observed that were double that expected from theory and systematics well established from measurements on the radiative excitation channel, that is, using nuclear resonance fluorescence (NRF). Additional strength as measured with NRF can only be present as heretofore unobserved branching or fragmentation of the scissors mode. Such possibilities were investigated in a transmission NRF measurement on the deforme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 21 publications
2
10
0
Order By: Relevance
“…It was suggested that the SR was rather weak and splits into two parts. From our work, it can be concluded that a weak SR is observed with split centroids located at 2.16 MeV ± 0.04 MeV and 2.91 MeV ± 0.05 MeV, in agreement with NRF measurements [67,68]. The case of 182 Ta is similar to that of 197,198 Au [76] where no SR is observed.…”
Section: Scissors Resonancesupporting
confidence: 88%
See 2 more Smart Citations
“…It was suggested that the SR was rather weak and splits into two parts. From our work, it can be concluded that a weak SR is observed with split centroids located at 2.16 MeV ± 0.04 MeV and 2.91 MeV ± 0.05 MeV, in agreement with NRF measurements [67,68]. The case of 182 Ta is similar to that of 197,198 Au [76] where no SR is observed.…”
Section: Scissors Resonancesupporting
confidence: 88%
“…8), which are found in the typical energy range for the SR [20]. From this work the distinction between M1 and E 1 is not possible but the assignment to the SR and its location in 181 Ta is corroborated by previous measurements [67,68].…”
Section: Scissors Resonancesupporting
confidence: 83%
See 1 more Smart Citation
“…(8). In experiments with quasi-monochromatic photon beams, a so-called 'average branching ratio' [42][43][44][45][46][47][48][49] of photoexcited states is often accessible, if discrete states cannot be resolved any more. It is defined as:…”
Section: A Definitionsmentioning
confidence: 99%
“…However, there are a number of experimental results which indicate violations of the BA hypothesis in the low-energy region. For example, the GSF in heavy deformed nuclei at excitation energies of 2 − 3 MeV is dominated by the orbital M1 scissors mode [16] and potentially large differences in B(M1) strengths are observed between γ emission and absorption experiments [17][18][19]. At very low energies (< 2 MeV) an increase of GSFs is observed in Oslo-type experiments [20,21], which for even-even nuclei cannot have a counterpart in ground state absorption experiments because of the pairing gap.…”
Section: Introductionmentioning
confidence: 99%